Quality Declared Seed for Sweetpotato: A Simplified Seed Inspection System for Haiti - Andrade-Piedra, J.L.; Paul, B.; Fuentes, S.; Ogero, K. (2024)
Sweetpotato is a staple food in Haiti, but yield is considerably lower than in neighboring countries. Low yield can be explained by several reasons, including low quality seed. Sweetpotato is a vegetatively propagated crop (VPC) and is multiplied primarily by vine cuttings. These cuttings are bulky, perishable, and susceptible to seed degeneration which makes seed production a challenge. Production and distribution of sweetpotato seed in Haiti is entirely farmer-based, with no formal seed system in place and no improved varieties. New germplasm from the International Potato Center (CIP, by its Spanish acronym) is being tested and it is expected that improved varieties will be available in few years. However, the full potential of these new germplasm, and of existing local varieties, will only be realized if farmers can access healthy seed. This document describes a simplified seed inspection system using the quality declared seed (QDS) scheme, with information from several countries in Africa. The purpose is to help commercial seed producers, the national seed authority, and local organizations that give support to commercial seed producers, such as non-governmental organizations (NGOs), universities, or farmers’ associations, to produce good quality seed at affordable prices in Haiti. It provides recommended practices for field selection, sourcing of planting materials, varieties, planting, agronomic practices, harvest and postharvest. It also provides standards for quality declaration, including composition of the inspection team, registration, seed classes (with a single seed class: QDS), visual inspection procedures, labels, costs, and tolerances for the two most important seed-borne pests and diseases in Haiti: the sweetpotato weevil (Cylas formicarius) and viruses: sweetpotato feathery mottle virus (SPFMV), sweetpotato leaf curl virus (SPLCV), sweetpotato chlorotic stunt virus (SPCSV), sweetpotato virus C (SPVC), and sweetpotato leaf curl virus (SPLCV) and related begomoviruses. Eventually, improved varieties will be released, and a more sophisticated seed inspection system could be designed, including more seed classes and more precise methods for estimating phytosanitary seed quality.